Empreendedorismo cultural em Camaçari/BA: um estudo para a formação de políticas públicas pautadas na indústria criativa - Oliveira, Halisson Deivid de Jesus (2024)
The objective of this research was to analyze how cultural entrepreneurship could guide the formation of public policies based on the creative industry in the municipality of Camaçari/BA. To meet this objective, this research was based on relevant studies on cultural entrepreneurship, the creative industry, the role of cultural entrepreneurs and the relationship between themes and public policies. Methodology: This is a research with a qualitative approach, of an exploratory and descriptive nature, using the case study method. For data collection, the semi-structured interview technique was used and with the collected material, content analysis was carried out and a technical report was prepared. Main Results: the study sought to provide better guidance on the articulations between cultural entrepreneurship and the formation of public policies to foster innovation and promote the sustainability of creative industries, generating employment and income in the municipality of Camaçari/BA. Theoretical, methodological and management contributions: this study contributes to highlighting the importance of forming public policies in the cultural sector for the growth of the local economy. The contributions of this research can also be presented in a broad way and capable of being replicated in contexts similar to the municipality explored. Relevance and Originality: the relevance lies in the innovative approach to cultural entrepreneurship as a vector for the formation of public policies aimed at creative industries in the municipality of Camaçari/BA, while the originality of the work lies in the integration of qualitative methods, such as case studies and content analysis, with a specific focus on the local context, allowing an in-depth understanding of the region's cultural and economic dynamics. Social/societal contributions: include the potential for the economic and social revitalization of Camaçari, through the promotion of creative industries that can generate employment, income and a greater appreciation of local cultural identity. Furthermore, this study offers a model that can be replicated in other regions with similar characteristics, expanding its impact and relevance for the formulation of public policies in different contexts.